High Dependency on Quacks – Is There a Gap in the Public Health Care Delivery System? Reflections from a District Located in the Thar Desert (India) - Singh, Alok Chauhan (Consilience, 2012)
This paper tries to analyse the availability and role of public health care services provided by the public sector in India. In addition, it also explores the reasons behind the high dependency on quacks in the study area. Data was acquired through in-depth interviews of 610 respondents with the help of a structured questionnaire from September to December 2010. Here, an attempt has been made to probe the pattern of utilization of health care services available at public health facilities by the sample respondents. It has been assessed in relation to socio-economic and demographic characteristics of the interviewees which exert significant influence on the utilization of health care facilities. The study finds that the number of CHCs/PHCs/Sub-centres in the study area is not adequate to meet the health needs (medical advice or treatment) of entire the population. The results recommend improving the availability and accessibility of health care facilities in the area under study.